2008
DOI: 10.1073/pnas.0707674105
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional analysis of vascularization during primary development of an organ, the gonad

Abstract: Time-lapse microscopy has advanced our understanding of yolk sac and early embryonic vascularization. However, it has been difficult to assess endothelial interactions during epithelial morphogenesis of internal organs. To address this issue we have developed the first time-lapse system to study vascularization of a mammalian organ in four dimensions. We show that vascularization of XX and XY gonads is a highly dynamic, sexually dimorphic process. The XX gonad recruits vasculature by a typical angiogenic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(173 citation statements)
references
References 41 publications
3
167
1
2
Order By: Relevance
“…Our method for tracking the behaviors of individual cells during tissue morphogenesis was useful both at the population level, where the dynamics of the collective population could be precisely quantified, as well as at the single-cell level, which highlighted the differences in behavior among individual cells. In our initial application of this method to studying the mechanism of microvasculogenesis, this method has provided, at the population level, additional granularity about how a system of endothelial cells form microvessels (33). For example, our observed sequence of events agrees with previous studies in which endothelial cells exhibited significant displacement before starting to elongate (14,15); in an in vivo study, endothelial cells also migrated into distinct spatial regions before undergoing morphological changes and vascular development (33).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our method for tracking the behaviors of individual cells during tissue morphogenesis was useful both at the population level, where the dynamics of the collective population could be precisely quantified, as well as at the single-cell level, which highlighted the differences in behavior among individual cells. In our initial application of this method to studying the mechanism of microvasculogenesis, this method has provided, at the population level, additional granularity about how a system of endothelial cells form microvessels (33). For example, our observed sequence of events agrees with previous studies in which endothelial cells exhibited significant displacement before starting to elongate (14,15); in an in vivo study, endothelial cells also migrated into distinct spatial regions before undergoing morphological changes and vascular development (33).…”
Section: Discussionsupporting
confidence: 81%
“…In our initial application of this method to studying the mechanism of microvasculogenesis, this method has provided, at the population level, additional granularity about how a system of endothelial cells form microvessels (33). For example, our observed sequence of events agrees with previous studies in which endothelial cells exhibited significant displacement before starting to elongate (14,15); in an in vivo study, endothelial cells also migrated into distinct spatial regions before undergoing morphological changes and vascular development (33). Our analysis is also consistent with studies that identified a period in which the vascular plexus underwent a slight deformation after formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…S6B), an Angiopoietin receptor expressed in macrophages associated with tumor neovascularization (36-38); and Tie2-Cre (Fig. S6C), as we previously reported using a Cre-responsive GFP reporter strain (39). Tie2-Cre is not expressed in hematopoietic cells of the yolk sac (40), suggesting that the expression of Tie2-Cre is not merely the result of the labeling of early hematopoietic progenitors but reflects de novo Tie2 expression within differentiated macrophages.…”
Section: Fetal Gonadal Macrophages Are Localized Near Developingmentioning
confidence: 55%
“…The vasculature plays an instructive role in testis morphogenesis (5)(6)(7)(8)39). The first step of this process, the breakdown of the mesonephric vascular plexus, is dependent on gonadal-mesonephric macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation